1995
DOI: 10.1086/175302
|View full text |Cite
|
Sign up to set email alerts
|

Fe II and Fe i Emission in IRAS 07598+6508 and PHL 1092

Abstract: One of the puzzles in understanding the spectra of active galactic nuclei (AGN) is the origin of the FeII emission. FeI emission, if present, will help reveal the physical conditions of the emitting gas. In an attempt to verify the presence of FeI lines, high S/N spectra of two FeII-strong quasars, IRAS 07598-6508 and PHL 1092, were obtained at the Multiple Mirror Telescope and the Steward 2.3 m Telescope. We have identified emission lines of FeI and TiII. The source of energy for FeII, FeI and TiII emission i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 15 publications
1
34
0
Order By: Relevance
“…In Figure 5, representing model u13h11, the predicted emission due to Fe i in the 2700-4500 8 region is, although quite weak, not entirely negligible. This is illustrated in the second panel from the top in Figure 5; the strongest transitions present in this figure are just those expected from the Fe i Grotrian diagram of Figure 1, namely decays from low-lying odd parity levels between $3.5 to 4.5 eV to the three lowest even parity states, the Kwan et al (1995) and in IRAS 07598+ 6508 by Kwan et al Both objects are Fe ii-strong quasars. The current calculations tend to support these identifications and the occurrence of Fe i transitions in some AGN spectra.…”
Section: Predicted Fe III Fluxesmentioning
confidence: 62%
See 1 more Smart Citation
“…In Figure 5, representing model u13h11, the predicted emission due to Fe i in the 2700-4500 8 region is, although quite weak, not entirely negligible. This is illustrated in the second panel from the top in Figure 5; the strongest transitions present in this figure are just those expected from the Fe i Grotrian diagram of Figure 1, namely decays from low-lying odd parity levels between $3.5 to 4.5 eV to the three lowest even parity states, the Kwan et al (1995) and in IRAS 07598+ 6508 by Kwan et al Both objects are Fe ii-strong quasars. The current calculations tend to support these identifications and the occurrence of Fe i transitions in some AGN spectra.…”
Section: Predicted Fe III Fluxesmentioning
confidence: 62%
“…Fe ii-strong quasars (Boroson & Green 1992;Kwan et al 1995). The Fe i atomic model consisted of 77 fine-structure levels (see Fig.…”
Section: Fe Imentioning
confidence: 99%
“…Models in which observed line width is based on orientation have recently been supported by evidence for a correlation between the ratio of the radio power and the monochromatic optical luminosity (an indication of the orientation angle) and the width of the Hb lines (Wills & Brotherton 1995). It has been postulated that the Fe II emission may arise in the accretion disk (Collin-Sou †rin, Hameury, & Joly 1988 ;Kwan et al 1995), so a face-on viewing angle would enhance the amount of Fe II observed.…”
Section: Models Based On Orientationmentioning
confidence: 97%
“…The Fe II emission in most AGNs is too strong to be explained by photoionization (Phillips 1978b;Kwan et al 1995); Fe II lines, and the other LILs as well, are more likely to be explained in the framework of collisional models where both the excitation of the lines and the ionization of the elements are due to collisions in a high density optically-thick medium illuminated mainly by hard X-rays; the Fe II emission region has a high density (10 10 < N e < 10 11 or 10 12 cm −3 ), a high column density (N H > 10 24 cm −2 ) and a low temperature (7500 < T < 10 000 K) (Collin-Souffrin et al 1980;1988b;Joly 1981;Clavel et al 1983;Collin-Souffrin & Lasota 1988;Kwan et al 1995). There is a significant correlation between Si III]/C III] and R 4570 ; Si III and C III have similar ionization potentials, but Si III] has a critical density more than one order of magnitude larger than C III] (1.1 × 10 11 and 5 × 10 9 cm −3 respectively); Si III]/C III] is thus a density indicator and becomes larger when density is higher; Si III]/C III] increases with increasing N e up to N e = 10 11 cm −3 (Aoki & Yoshida 1999;Wills et al 1999;Kuraszkiewicz et al 2000).…”
Section: High-and Low-ionization Linesmentioning
confidence: 99%